Receptor tyrosine kinase expression and phosphorylation in canine nasal carcinoma - Hocker, Samuel (Kansas State University, 2018)
This study evaluated sixteen canine nasal carcinoma and five normal nasal epithelium samples for expression and phosphorylation of known targets of toceranib [vascular endothelial growth factor receptor-2 (VEGR2), platelet derived growth factor alpha (PDGFR-[alpha]), platelet derived growth factor receptor beta (PDGFR-[beta]), and stem cell factor receptor (c-KIT)] and epidermal growth factor receptor 1 (EGFR1) using immunohistochemistry, RT-PCR and a receptor tyrosine kinase (RTK) phosphorylation panel. Protein for VEGFR2 was expressed in neoplastic cells of all carcinomas, PDGFR-[alpha] was noted in 15/16, whereas PDGFR-[beta] was detected in 3/16 samples, but showed primarily stromal staining. Protein expression for c-KIT was present in 4/16 and EGFR1 was noted in 14/16 samples. Normal tissue showed variable protein expression of the RTKs. Messenger RNA for VEGFR2, PDGFR-[beta], and c-KIT were noted in all samples. Messenger RNA for PDGFR-[alpha] and EGFR1 were detected in 15/16 samples. All normal nasal tissue detected messenger RNA for all RTKs of interest. Constitutive phosphorylation of VEGFR2, PDGFR-[alpha], PDGFR-[beta] and c-KIT was not observed in any carcinoma or normal nasal sample, but phosphorylation of EGFR1 was noted in 10/16 carcinoma and 3/5 normal samples. The absence of major phosphorylated RTK targets of toceranib suggests the clinical effect of toceranib may occur through inhibition of alternative and currently unidentified RTK pathways in canine nasal carcinomas. The observed protein and message expression and phosphorylation of EGFR1 in the nasal carcinoma samples merits further inquiry into EGFR1 as a therapeutic target for this cancer.
Keywords: Canine; Nasal carcinoma; Receptor tyrosine kinase; Phosphorylation